Tigers fighting back - Ballance, Alison; NHNZ in association with National Geographic Channel International (Dunedin, N.Z. : Natural History New Zealand, 2010)
Biologists working for the Wildlife Conservation Society in the far east of Russia, the Indonesian jungle and India's forest, work to save the tiger from extinction. Over the last century the population of tigers have plummeted by 95 percent due to poaching, the demise of free land space and the demand for medicine made from tigers. The challenge to give them food, room and protection to ensure the survival of tigers is an issue each government must face as they tailor their own rescue packet to suit local conditions. Wildlife Conservation workers unite by a common passion to give tigers a fighting chance and restore their population.
Keywords: Tiger -- India; Tiger -- Indonesia; Tiger -- Russia (Federation) -- Russian Far East